Employee Morale and Its Impact on Employee Efficiency in Spinning Mills With Reference to Coimbatore District - Nandhini, M.; Usha, M.; Palanivelu, P. (International Research Journal of Management, IT & Social Sciences, 2015)
Employee morale is defined by the employees outlook, optimism, self-concept, and assured belief in themselves and their organization, its mission, goals, defined path, daily decisions, and employee appreciation. Faith in self and faith in their organization are both important factors in positive employee morale. Individualâs morale is related with knowing oneâs own expectations and living up to them. If one is clear of his own needs and how to satisfy them most of the time, his morale is height. Individualâs morale is single personâs attitude towards life. While group morale reflects the general expert de corps of a collective group of personalities. Spinning mills in Tamil Nadu were running round the clock, and were busy expanding their operational capacities. Now, with the export market hit the economic crisis, coupled with a few other factors, the declining foreign orders has pushed the textile industry of South India is centered into a crisis.